Menyoal Narasi Kesadaran Lingkungan Melalui Buku Teks Pelajaran Sejarah Di SMA - Yuver Kusnoto (JURNAL HISTORICA, 2022)
This article aims to: (1) identify themes about the environment in history textbooks in high school grades X, XI, 2013 curriculum and XII SMA/MA Education Unit curriculum (KTSP); (2) analyze the representation of environmental problems in textbook material. This research was conducted using qualitative methods and analyzed using content analysis techniques. The object of research is textbook material published by the Ministry of Education and Culture in 2009 and 2001. Data collection and data analysis were carried out using content analysis techniques. Based on the research conducted, the results show that: (1) there are themes that can strengthen environmental awareness in students who study history in class X, XI in the 2013 curriculum and class XII science in the Education Unit curriculum (KTSP); (2) For class XII in the 2013 curriculum the discussion of environmental history is not too much. There is only one sub-topic about the green revolution. The availability of materials with environmental history narratives can also be strengthened by narratives from the results of research conducted by historians who focus on environmental history studies. Keywords: Environmental Awareness Narrative, History Textbook